Drug interactions in the assessment of bleeding risk with oral anticoagulant therapy - Kovačević, Milena (Archives of Pharmacy, 2022)
Oral anticoagulants (OACs) have a significant place in the treatment of patients with atrial fibrillation (AF), as they reduce the stroke risk by 60-70%. Various bleeding risk assessment tools were developed to assess the OACs benefit/risk ratio. The study aimed to assess the bleeding risk using HAS-BLED, ATRIA and ORBIT scores in patients with AF on OACs. Additionally, potential clinically significant drug-drug interactions (DDIs) that may further increase the risk of bleeding have been identified. A retrospective observational study was conducted at the cardiology department of the Clinical Hospital Center Bežanijska kosa. LexiInteract database was used to assess DDIs. The study included 124 patients. A high risk of bleeding was identified in 10.5% using HAS-BLED, in 4.8% using ATRIA, while no patient was marked as high-risk using the ORBIT score. The prevalence of DDIs that may further increase the risk of bleeding was 18.5%. Six different types of DDIs with vitamin K antagonists have been identified: antidepressants, drugs for hyperacidity, hypothyroidism, antidiabetics, statins and propafenone. DDIs were classified as risk class C, ie they require increased patient monitoring or dose adjustment. The disadvantage of the risk classification in the LexiInteract database is that the presence of other risk factors is not considered, which may increase the possibility of adverse outcomes. For example, cardiovascular disease has been identified as a factor of the pharmacokinetic and pharmacodynamic variability of drugs. DDIs assessment can contribute to a better understanding of the risks of OACs use and improvement in the care of patients.